Domains of health-related quality of life in age-related macular degeneration: a qualitative study in the Chinese cultural context. Issue 4 (17th April 2018) - Bian, Wei; Wan, Junli; Smith, Graeme; Li, Shiying; Tan, Mingqiong; Zhou, Fengjiao
Abstract : Objective: To explore which areas of health-related quality of life were affected in Chinese patients, and to identify whether the areas are well covered by validated questionnaires. Design: A qualitative study based on semistructured interviews was conducted. A qualitative thematic analysis following the approach of Colaizzi was used to analyse the interview data for significant statements and phrases. The themes and subthemes organised from the analysis were then compared by using the following current instruments: National Eye Institute Visual Function Questionnaire (NEI-VFQ-25), Macular Disease Quality of life Questionnaire (MacDQoL) and Low-Luminance Questionnaire (LLD). Participants and setting: Twenty-one patients with age-related macular degeneration were recruited from the eye clinic of Southwest Eye Hospital in Chongqing, mainland China. Results: The mean age of the participants was 69.8 years (range 57–82 years) and the duration of the disease ranged from 3 months to 6 years. The qualitative analysis revealed nine important domains including symptoms, difficulties with daily activities, depending on others, depression and uncertainty, optimism and hope, social isolation, role change, family support and financial burden. However, all the three questionnaires were insufficient to capture the full extent of quality of life issues of Chinese patients with AMD, and MacDQoL covered more domains when compared with NEI-VFQ-25 and LLD. Conclusion: The domains of concepts important to people with AMD in the Chinese culture are not fully represented in the three widely used questionnaires. Nine important domains were identified for the assessment of quality of life and should be considered when assessing the impact of AMD on Chinese individuals. Further studies are needed to develop an AMD quality of life questionnaire, better tailored to the needs and culture of Chinese patients.